Studi Literatur: Depresi dan Konflik Selama Kehamilan Dikaitkan dengan Meningkatnya Peluang Terjadinya Stunting - Hardiyati Hardiyati; Supratti Supratti (Politeknik Kesehatan Kemenkes Mamuju, 2021)
According to the United Nations Children's Fund, it is estimated that worldwide around 165 million children were stunted in 2012. West Sulawesi currently has the highest prevalence of stunting (41.6 per cent), behind the WHO standard, which is below 20 per cent. Currently, the efforts that can be made by the Government of Indonesia are to target nutrition improvement in sustainable development (SDGs). This literature study aims to provide an overview of how depression and other problems during pregnancy can be associated with stunting. Literature from ProQuest, Science Direct and Google Scholar databases. The results showed that the 13 articles reviewed stated that depression and conflict during pregnancy were associated with an increase in stunting rates. An illustration of how depression and other problems during pregnancy can be used as a reference in implementing more diverse and appropriate interventions, especially in the region of one of the provinces in Indonesia, namely West Sulawesi, which has a high prevalence of stunting.